2014
DOI: 10.1638/2011-0261r3.1
|View full text |Cite
|
Sign up to set email alerts
|

DIET COMPOSITION, FOOD INTAKE, APPARENT DIGESTIBILITY, AND BODY CONDITION SCORE OF THE CAPTIVE ASIAN ELEPHANT (ELEPHAS MAXIMUS): A PILOT STUDY IN TWO COLLECTIONS IN THAILAND

Abstract: Limited data are available regarding the nutrition and feeding of captive Asian elephants in range countries. In this study, feeding regimens of two collections in northern Thailand and their actual diets shaped by availability of forage and mahout preferences were assessed for nutritional quality. The composition of dietary intake, fecal output, and the dietary regimen were individually recorded for 5 days in 10 elephants. The proportion of forage in the diet represented 41 to 62% of the dry matter intake (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
(7 reference statements)
0
13
0
Order By: Relevance
“…60% of DM), and gut passage rate ( c . 21–46 hours for African elephants compared to 55 hours for Asian elephants, depending on substrate consumed) support the use of the horse as a physiologic model in feeding programmes (see Clauss, Loehlein et al ., for summary; Romain et al ., ; Das et al ., ), although elephant digestion coefficients are generally lower than horses because of their faster gastrointestinal passage rates.…”
Section: Nutritionmentioning
confidence: 98%
See 2 more Smart Citations
“…60% of DM), and gut passage rate ( c . 21–46 hours for African elephants compared to 55 hours for Asian elephants, depending on substrate consumed) support the use of the horse as a physiologic model in feeding programmes (see Clauss, Loehlein et al ., for summary; Romain et al ., ; Das et al ., ), although elephant digestion coefficients are generally lower than horses because of their faster gastrointestinal passage rates.…”
Section: Nutritionmentioning
confidence: 98%
“…Certainly zoo-based research has contributed to our knowledge of elephant digestive physiology through controlled studies. Basic investigations of intake [1-2% of body weight on a dry matter basis (DMB)], digestion (average 40-50%, range 20% to c. 60% of DM), and gut passage rate (c. 21-46 hours for African elephants compared to 55 hours for Asian elephants, depending on substrate consumed) support the use of the horse as a physiologic model in feeding programmes (see Clauss, Loehlein et al, 2003 for summary;Romain et al, 2014;Das et al, 2015), although elephant digestion coefficients are generally lower than horses because of their faster gastrointestinal passage rates.…”
Section: Digestive Physiology and Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that all the elephants met the recommended DMI and variable digestible energy. However, DMI is less informative than is digestible energy intake (Romani et al 2014). Increased NDF digestibility will result in higher energy values, and perhaps more importantly, increased forage intakes.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this DE: ME ratio, the relative DE intake recommendations thus become 0.68 (DE) MJ per kg per day. This estimate of relative DE for maintenance was used to assess the adequacy of DE intake in the current study because it is commonly used to evaluate requirements of other hindgut fermenters such as horses, rhinos and tapirs (Romani et al 2014).…”
Section: Energy Intake and Balancementioning
confidence: 99%